New Media Technology in Developing Effective Organizational Internal Communication - Nur Kholisoh; Ria Sulastri (Bina Nusantara University, 2017)
The article was intended to investigate various benefits of Whatsapp Messenger application for an effective intenal communication in PT Euro Management Indonesia. In addition, this research also aimed to map the organizational internal communication pattern through the use of Whatsapp Messenger application. The research used theories of organizaional communication, new media communication pattern, and computer mediated communication (CMC). Moreover, paradigm used in the research was constructivist with qualitative approach and the research method was case study. The research result finds that the use of new media Whatsapp Messenger as a tool of communication can build effective internal communication in PT Euro Management Indonesia. Moreover, it also shows that the internal organizational communication pattern in PT Euro Management Indonesia used in Whatsapp Messenger application is conversation pattern.